Penerapan Algoritma Dynamic Priority Scheduling pada Antrian Pencucian Mobil - Rizki Setyawati; Adam Bachtiar Maulachela (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
Queue is a condition where the number of service recipients is higher than the number ofservice providers. This condition can cause a buildup of service recipients, and eventually,bottlenecks will occur. It faced by all service organizations that focus on service to customers.No exception is a car wash business whose business processes focus on providing fast andquality car wash services. But unfortunately, many car wash businesses get complaints fromcustomers, especially related to the queue buildup and unclear queue information received bycustomers. Therefore this study aims to produce a mobile-based car wash queue application,which includes a dynamic priority scheduling algorithm that functions as a queue manager.To carry out these objectives, a research methodology that is sequential and iterative used,namely, the software development methodology using the Rapid Application Development(RAD) model. This model consists of four phases: planning needs, prototype development,system development, and finally, testing. The Application test is finished with two approaches,namely testing of application code, specifically the application of dynamic priority schedulingalgorithm and testing of the overall functional system. From the test results, it knows that thecar wash queue application managed to sort customer orders based on the specified priorityrules based on the distance and time of the law. While the results of testing the systemfunctionality show that the application successfully manages a variety of errors, both causedby system failures and due to human error.